Relationship of the epithelial-mesenchimal transition expression markers with clinical and morphological parameters of colon cancer - L. E. Sinyanskiy; N. V. Krakhmal; S. S. Naumov; S. V. Patalyak; S. G. Afanasyev; S. V. Vtorushin (Сибирский онкологический журнал, 2022)
The treatment of colon cancer with a mesenchymal-like phenotype poses a great challenge. Purpose of the study: to research expression of FRMD6, ZEB1, HTR2B, CDX2 in the primary tumor tissue with relation of the clinical and pathological features of colon cancer. Material and methods. a combined analysis of the expression of FRMD6, ZEB1, HTR2B, CDX2 with pathological criteria was performed in 100 patients with T1–4bN0–2bM0  colon  cancer.  Results  of  the  study  show  that  tumors  with  mesenchymal  signs  are characterized by a large size of the primary tumor, a high grade of differentiation, regional metastases, and eventually advanced stage of the disease. The frequency and expression levels of FRMD6, ZEB1 and HTR2B are depended of grade of adenocarcinoma. in cases with positive expression and a high percentage of expression of these proteins in the cancer cells, the degree of tumor morphological anaplasia increases. Conclusion. The study made it possible to reveal the relationship of IHC markers (FRMD6, ZEB1, HTR2B, CDX2) with tumor characteristics that determine the outcome. The studied markers may have prognostic and predictive value in treatment approaches of colon cancer.